Pendampingan dan pembekalan teknik perekrutan sumber daya manusia dan digital marketing pada UMKM konveksi - Edi Sugiono; Santi Retno Sari; Dita Nurul Aini Mustika Dewi (LPMP Imperium, 2023)
This community service activity aims to provide training and assistance to improve skills and understanding of HR recruitment and digital marketing for convection MSME actors in West Java. The activity was carried out for approximately 4 days. MSME actors who became participants totaled 33 participants. The responses of the webinar participants gave positive responses regarding this training. The participants really did not understand recruitment, especially online recruitment. Likewise, from the results of this service it is known that the skills and knowledge regarding digital marketing of the participants are still minimal. Suggestions need further training that is more implementable and more intense assistance. Furthermore, further training is needed regarding the application and implementation of online recruitment with the application.